An Investigation on Shape Morphing by Modulus Variation: Forward Approach - Amin Mohaghegh Motlagh; William W. Clark (Journal of Engineering)
Structural shape deformation, in its conventional way, includes applying forces to a fixed-compliance structure to deform it to certain shapes. Rather than addressing shape control in the established way (applying forces to elastically or plastically deform a structure), this work studies the use of shape morphing, which involves combining applied forces and local modulus changes. Specifically in this paper, a simply supported elastic beam that can exhibit variable compliance behavior is selected as the model. This study focuses on the forward approach of morphing, that is, determining possible beam shapes due to the applied force and modulus variability. The goal is to incorporate variable-modulus materials into a structure model and utilize the controllable modulus change to quantify the morphing of the structure with limited actuator numbers, locations, and force levels. The resulting morphed shapes are quantified in terms of various characteristic parameters. The study demonstrates that a larger, and in some cases nonintuitive, space of shapes becomes possible when modulus change is utilized, for the same set of applied forces.